THE MAIN PERSPECTIVES OF THE QUALITY OF LIFE OF STUDENTS IN THE SECONDARY CYCLE: AN OVERVIEW OF OPPORTUNITIES, CHALLENGES AND ELEMENTS OF GREATEST IMPACT - de Sousa Alvarenga, Ana Beatriz Cardoso; Espuny, Maximilian; da Motta Reis, José Salvador [UNESP]; Silva, Fernanda De Oliveira; Sampaio, Nilo Antonio De Souza; Nunhes, Thaís Vieira [UNESP]; Barbosa, Luís César Ferreira Motta; Santos, Gilberto; de Oliveira, Otávio José [UNESP] (Faculty of Engineering, University of Kragujevac, 2021)
The level of Quality of Life (QoL) influences and reflects some elements of student health and impacts on academic performance. The objectives of this study were to analyze content to identify the main research opportunities and challenges on the qualityoflifeof students aged 15 to 16 years in public and private schools, and to verify if there is a correlation between student QoL, social, economic, and educational indicators. The methods adopted in this research were bibliographic research, content analysis and multivariate statistical analysis. The academic contribution of this work was the articulation of a theory on student quality of life, and the applied contribution was subsidy for the government and educational institutions to elaborate strategies, considering the correlations between the economic, social and educational variables.
Keywords: Qualityof Life; School Performance; Student; Student Quality of Life